1980
DOI: 10.1063/1.439210
|View full text |Cite
|
Sign up to set email alerts
|

A new method for observing the rotational spectra of weak molecular complexes: KrHCl

Abstract: A new method of observing the rotational transitions of weak molecular complexes by combining the techniques of microwave Fourier transform spectroscopy, a Fabry–Perot cavity, and a pulsed nozzle source of molecules is described. High resolution and good sensitivity are achieved. Twelve isotopic species of the KrHCl molecule involving all combinations of the 86Kr, 84Kr, 82Kr, H, D, 35Cl, and 37Cl isotopes are assigned and the rotational constants, Cl nuclear quadrupole coupling constants, and centrifugal disto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…The Fourier transform microwave spectrometer is based on the design of Flygare et al (7,8) and the details have been reported elsewhere (9,10). The main features are described briefly below.…”
Section: Methodsmentioning
confidence: 99%
“…The Fourier transform microwave spectrometer is based on the design of Flygare et al (7,8) and the details have been reported elsewhere (9,10). The main features are described briefly below.…”
Section: Methodsmentioning
confidence: 99%
“…Spectra were recorded using a Fourier transform microwave spectrometer, based on the design of Flygare et al [9,10], the details of which have been reported previously [11,12]. The main features of the instrument are described briefly below.…”
Section: Methodsmentioning
confidence: 99%
“…The microwave spectrum of OCHBr was recorded by using the Fabry-Perot Fourier transform spectrometer (5,6,8). The OCHBr dimers were formed by pulsing a mixture of 4% CO and 4% HBr in Ar through a 0.5-mm supersonic nozzle into the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…A method for the measurement of the molecular properties of transient and other weakly bound molecular species has been developed'by applying Fourier transform techniques in the microwave frequency range (1)(2)(3)(4). The method combines the principles of the pulsed Fourier transform microwave technique, a Fabry-Perot cavity, and synchronization of the microwave pulse with a pulsed supersonic-nozzle beam of a gaseous mixture used to generate, in this case, weak van der Waals molecular complexes (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation